An Analysis Of 20 KV Distribution Reliability System At PT. PLN ULP Tanjungbalai - Bastian Radol Pardede; Dicky Lesmana; Siti Anisah (Jurnal Scientia, 2024)
This paper analysed the reliability of the 20 kV distribution system at PT. PLN ULP Tanjung-balai. The reliability of the electricity distribution system is crucial to ensure a stable power supply with minimal interruptions to consumers. The study aims to identify and evaluate the factors affecting the reliability of the 20 kV distribution network and propose solutions to enhance the system’s reliability. The methods used in this study include the collection of historical outage data, analysis of network performance, and calculation of reliability indices such as SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index), and CAIDI (Customer Average Interruption Duration Index). Additionally, the study utilizes network analysis software to simulate the operational conditions of the distribution network. The results of the study indicate that the reliability of the distribution system at PT. PLN ULP Tanjungbalai requires improvement, particularly in reducing the frequency and duration of power outages. Several identified causes of outages include extreme weather conditions, equipment failures, and external factors such as animals or vegetation. To improve system reliability, several actions are recommended, such as more intensive preventive maintenance, modernization of distribution equipment, and enhanced monitoring of the distribution network.